ترجمة الضمائر في القرآن الكريم الى الانكليزية (University of Mosul-college of Basic Education, 2009)
يستقصي هذا البحث ترجمة الضمائر في القرآن الكريم الى اللغة الانكليزية، ويحاول البحث - مستنداً الى التفاسير القرآنية - دراسة كيفية تعامل مترجمي القرآن الكريم مع الضمائر والأسماء التي تشير إليها وذلك بالتحقق من مدى دقة ترجماتهم . وقد تبين بأن المترجمين لم يعيروا الضمائر الاهتمام اللازم ، ولذلك يؤكد البحث على الإيصاء بتنقيح هذه الترجمات على قدر تعلق الأمر بالضمائر.This research investigates the translation of pronouns in the Glorious Qur'an into English. Based on the Qur'anic interpretations, the research tries to examine how translators of the Glorious Qur'an deal with pronouns and their antecedents by checking the accuracy of their renderings. It is found that pronouns are given little attention on the part of translators. Hence, revising translations, as far as pronouns are concerned, is strongly recommended.